DIHAR SITARLAK PADA MASYARAKAT SIMALUNGUN : KAJIAN SEMIOTIK - Sari Mega Florensia Simanungkalit; Nurwani Nurwani; Iskandar Muda (Universitas Negeri Medan, 2018)
Abstract−This study examines the semiotics contained in diharsitarlak in Simalungun society. The goal is to explore the meaning contained in the sararar and interpretation of meaning seen through the theory of semiotics. Sitarlak is a martial arts that comes from Simalungun who became the performing arts for the community that is as a welcome dance for accompanied by music and using a special outfit. The theory used relates to the research topic of Suzanna K. Langer theory which discusses the motion and the theory of semiotic de Saurrsure to express the meaning. The research time used to discuss the semiotics was held in Simalungun society was done for 2 months ie end of August until October 2017. The research place was SanggarTortor Elak-elak in Kelurahan Sirpang Dalig Raya, Raya Subdistrict, Simalungun Regency. Population in this research is artist as well as adat character, sambual (pemusik), pandihar (people who bersilat) who understand about diharsitarlak. Data collection techniques include literature study, observation, interview and documentation, and then analysis with qualitative descriptive method. Based on the research conducted, the form of diharsitarlak is a series of silat movements consisting of 7 main motifs yaitu sombah, throw boxing worship, marsimbur, mangindo (top level), mangindo (lower level), lakkasitolu-tolu and cover worship. Clothing that is used in the sitarlakdihar is long shirt and trousers (black, red, and mixture of black, white, red), yeast pane, suri-suri, and gotong salalu. The accompaniment of music on the sitarlakdihar gondrang haro-day, parahot, and gual porang. As for the semiotics contained in the scarred sitarlak poured through the sign (sign) seen from the form of motion in the series of presentation, marker (signifier) is a form of motion as the main motive in the diharsitarlak, and signified (signified) is the meaning contained in diharsitarlak. So it can be interpreted the overall meaning in the absolute sarar is the actualization of life of the people of Simalungun in various conditions, such as giving thanks to God, facing temptation, being polite and humble, respecting and appreciating others. Keywords: semiotics, signs, signifer, signified, diharsitarlak